K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

7 tháng 3 2021

x8 + 3x4 + 4

= ( x8 + 4x4 + 4 ) - x4

= ( x4 + 2 )2 - ( x2 )2

= ( x4 - x2 + 2 )( x4 + x2 + 2 )

7 tháng 3 2021

\(=x^8+4x^4+4-x^4\)

\(=\left(x^4-2\right)^2-x^4\)

\(=\left(x^4-x^2-2\right)\left(x^4+x^2-2\right)\)

\(=\left(x^4-2x^2+x^2-2\right)\left(x^4+2x^2-x^2-2\right)\)

\(=\left(x^2\left(x^2-2\right)+x^2-2\right)\left(x^2\left(x^2+2\right)-\left(x^2+2\right)\right)\)

\(=\left(x^2+1\right)\left(x^2-2\right)\left(x^2-1\right)\left(x^2+2\right)\)

\(=\left(x-1\right)\left(x+1\right)\left(x^2+1\right)\left(x^2-2\right)\left(x^2+2\right)\)

2 tháng 1 2016

x8+3x4+4

= x8+4x4+4-x4

= (x4+2)2-(x2)2

= (x4+2-x2).(x4+2+x2)

2 tháng 1 2016

\(x^8+3x^4+4=(x^8+3x^4)+4=x^4(x^2+3)+4=(x^2+3)(x^4+4)\)

12 tháng 11 2021

=4x2-4=4(x2-1)=4(x-1)(x+1)

12 tháng 11 2021

4(x2-1)

a: \(x^4+x^2+2x+6\)

\(=x^4-2x^3+3x^2+2x^3-4x^2+6x+2x^2-4x+6\)

\(=\left(x^2-2x+3\right)\left(x^2+2x+2\right)\)

16 tháng 7 2021

\(x^4-3x^3-x+3\)

\(=x^4-x^3-2x^3+2x-3x+3\)

\(=\)\(x^3\left(x-1\right)-2x\left(x^2-1\right)-3\left(x-1\right)\)

\(=x^3\left(x-1\right)-2x\left(x-1\right)\left(x+1\right)-3\left(x-1\right)\)

\(=\left[x^3-2x\left(x+1\right)-3\right]\left(x-1\right)\)

\(=\left[x^3-2x^2-2x-3\right]\left(x-1\right)\)

\(=\)\(\left[x^3-3x^2+x^2-3x+x-3\right]\left(x-1\right)\)

\(=\left[x^2\left(x-3\right)+x\left(x-3\right)+\left(x-3\right)\right]\left(x-1\right)\)

\(=\left[\left(x-3\right)\left(x^2+x+1\right)\right]\left(x-1\right)\)

16 tháng 7 2021

\(x^4-3x^3-x+3\)

\(x\left(x-3\right)-\left(x-3\right)\)

\(\left(x-1\right)\left(x-3\right)\)

25 tháng 5 2015

a) x8 + x + 1 = (x^2+x+1)*(x^6-x^5+x^3-x^2+1)

b) x^8 + 3x^4 + 4 = (x^4-x^2+2)*(x^4+x^2+2)

2 tháng 11 2018

\(x^8+x+1\)

\(=x^8+x^7+x^6-x^7-x^6-x^5+x^5+x^4+x^3-x^4-x^3-x^2+x^2+x+1\)

\(=x^6\left(x^2+x+1\right)-x^5\left(x^2+x+1\right)+x^3\left(x^2+x+1\right)-x^2\left(x^2+x+1\right)+x^2+x+1\)

\(=\left(x^2+x+1\right)\left(x^6-x^5+x^3-x^2+1\right)\)

9 tháng 9 2023

\(x^3-3x^2+6x-4\)

\(=x^3-2x^2+4x-x^2+2x-4\)

\(=\left(x^3-2x^2+4x\right)-\left(x^2-2x+4\right)\)

\(=x\left(x^2-2x+4\right)-\left(x^2-2x+4\right)\)

\(=\left(x-1\right)\left(x^2-2x+4\right)\)

9 tháng 9 2023

x^3 - 3x^2 + 6x - 4 

<=> x^3-3x^2+3x-1+3x-3

<=>(x-1)^3+3(x-1)

<=>(x-1)+((x-1)^2+3)

<=>(x-1)+(x^2-2x+4)

20 tháng 7 2016

\(x^8+3x^4+4\)

\(=x^8+4x^4+4-x^4\)

\(=\left(x^4-2\right)^2-x^4\)

\(=\left(x^4-x^2-2\right)\left(x^4-x^2-2x^2-2\right)\)

\(=\left(x^2-2\right)\left(x^2+1\right)\left(x^2-1\right)\left(x^2+2\right)\)

\(=\left(x-1\right)\left(x+1\right)\left(x^2-2\right)\left(x^2+1\right)\left(x^2+2\right)\)

20 tháng 7 2016

x8+3x4+4=(x8+4x4+4)-x4=(x4+2)2-x4=(x4+2-x2)(x4+2+x2)

29 tháng 7 2021

Trả lời:

a, x4 + 3x3 + x2 + 3x

= ( x4 + 3x3 ) + ( x2 + 3x )

= x3 ( x + 3 ) + x ( x + 3 )

= ( x3 + x ) ( x + 3 )

= x ( x2 + 1 ) ( x + 3 )

b, Sửa đề: x4 - x2 + 8x - 8

= ( x4 - x2 ) + ( 8x - 8 )

= x2 ( x2 - 1 ) + 8 ( x - 1 ) 

= x2 ( x - 1 ) ( x + 1 ) + 8 ( x - 1 )

= ( x - 1 ) [ x2 ( x + 1 ) + 8 ]

= ( x - 1 ) ( x3 + x2 + 8 )

29 tháng 7 2021

x+ 3x+ x2 + 3x = x3(x + 3) + x(x + 3)
= (x + 3)(x2 + 1)x